SYSTEMATIC ANALYSIS OF ENTOMOPHAGES OF COCCIDS OF ORCHARDS (ON THE EXAMPLE OF EASTERN FERGANA REGION) (Scientific journal of the Fergana State University, 2024)
The article systematically analyzes natural coccidiosis of orchards. The total number of coccids and entomophagus in the orchards of the Eastern Fergana region is 53 species. 41.5% (22 species) of identified species are coccids and 58.5% (31 species) are entomophages. Pest coccids living in fruit trees and shrubs consist of 22 species belonging to 17 genera in 4 families. The natural group of these coccids consists of 31 species belonging to 26 genera of 12 families belonging to 3 families.